Causal Model of the Influence of Instructional Leadership, Teacher Competence, and Work Culture for Educational Quality in Public Junior High Schools - Widayati, Wiwik; Maryanto; Egar, Ngasbun (Jurnal Ilmiah Pendidikan Profesi Guru, 2025)
Despite extensive process improvement efforts, educational quality often lags, indicating a gap between managerial routines and uneven learning outcomes. Closing this gap requires an integrated perspective that links instructional leadership, teacher professional competence, and work culture as a single quality system. This study aimed to analyze the causal model of the influence of instructional leadership, teacher competence, and work culture on educational quality in public junior high schools. This study used a quantitative correlational design with proportional random sampling of 173 teachers. Data were collected through validated and reliable questionnaires and analyzed using descriptive statistics, correlation, multiple regression, and path analysis; all analytical assumptions were met. The results showed that all three constructs were positively and significantly associated with educational quality; simultaneously, the model explained a significant portion of the variation, with teacher competence emerging as the strongest predictor. The path analysis showed that leadership influences operate directly and indirectly through teacher competence and work culture, making synergy between constructs key. This study validates the integrated causal model of school quality. Theoretically, the findings clarify the pathways of influence between components. In practical terms, the implication is that the quality improvement agenda needs to combine programmed leadership routines, practice-based professional development, and the cultivation of collaboration, innovation, and disciplined, sustainable, and accountable follow-up.